MOTIVASI ORANGTUA MEMILIH LEMBAGA BIMBINGAN BELAJAR ANAK HEBAT (AHE) - Fallah, Riffa Nurlita; Syafrida, Rina; Riana, Nancy (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
Parents are the main and initial teachers for their children, the job of parents at home is to help their children learn and grow optimally. However, in this day and age, many parents work, which means that children's development, especially cognitive ones, are less stimulated. This research aims to determine the motivation of parents in choosing the Great Children's Tutoring Institute (AHE) as an additional educational institution for their children. This research uses a qualitative approach with narrative descriptive methods, in-depth data collection for this research uses purposive sampling techniques, research data is collected through observation, interviews and documentation. The research results show that parents' motivation in choosing AHE is (a) the need to do something for activities, (b) the need to achieve results, namely achievement, and (c) the need to overcome difficulties. Parents believe that AHE provides quality learning services and effective learning methods, a positive and interactive learning environment and special programs for orphans are additional attractions.